METHODICAL PRINCIPLES OF EVALUATION OF PRICE MANAGEMENT IN THE ENTERPRISE FINANCIAL MANAGEMENT SYSTEM - SHYSHKOVA, YULIA; PARFENYUK, EVGENIUA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article presents the results of development and testing of the author's methodological approach to the analysis and evaluation of the quality of pricing management for industrial products.The purpose of the article is to develop a methodological approach and evaluate the management of pricing in the financial management system of the enterprise.Positive and negative aspects of strategic pricing management for the enterprise 's products are revealed. It is proposed to take into account the coefficient of price elasticity as an important analytical characteristic, on the one hand, analyzing the quality of pricing management in the financial management system of business, and, on the other - planning prices for products.Examples of analysis are given: 1) structural elements of the price and level of profitability of enterprise products; 2) the share of certain types of products in the total net income from sales, the level of wholesale and sales surcharges and profits, the impact of changes in the latter on the level of operating profit of industrial enterprises. Conclusions are made on further development of the system of analysis of pricing of products in the system of financial management of the enterprise.The applied significance of the research results is that using the author's methodological approach it is possible to identify the results and consequences of establishing a level of product prices for key parameters of the financial management system - profit and profitability, and for different products simultaneously.The scientific novelty of the research results is the introduction into scientific circulation of the concept of "price elasticity coefficient", which reflects changes in the financial management system depending on the change in unit price by 1%.
Keywords: financial management; pricing; management quality assessment; methods of analysis; development of industrial enterprises